1989
DOI: 10.1177/030802268905201209
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Portable Ramps

Abstract: This article summarises the findings of a study which aimed to evaluate a selection of commercially available portable ramps in the United Kingdom. The ramps were tested by wheelchair users and ambulant disabled people, in order to assess ease of use, safety and user acceptance. Some points which should be taken into consideration when recommending or selecting a portable ramp are highlighted. Table I. Portable ramps included for evaluation METHODOLOGY AIM commercially available portable ramps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Since 1977, there have also been some significant advances in wheelchair seating and mobility technology, notably the introduction of midwheeldrive power chairs, seating and positioning systems that allow more severely-impaired individuals to travel independently, and wheelchair frames that accommodate larger and heavier people (Steinfeld et al 2010). Sweeney et al (1989) evaluated 13 portable ramps ranging from 1:12 to 1:3 with 45 participants representing a diverse age range, wheeled mobility devices, and functional levels. The authors reported that ramp slopes of 1:12 to 1:7 could be negotiated with "relative ease" by 88% of the self-propelling manual wheelchair users (n=18), compared to 52% of the same group for the 1:6 slope.…”
Section: Previous Ramp Researchmentioning
confidence: 99%
“…Since 1977, there have also been some significant advances in wheelchair seating and mobility technology, notably the introduction of midwheeldrive power chairs, seating and positioning systems that allow more severely-impaired individuals to travel independently, and wheelchair frames that accommodate larger and heavier people (Steinfeld et al 2010). Sweeney et al (1989) evaluated 13 portable ramps ranging from 1:12 to 1:3 with 45 participants representing a diverse age range, wheeled mobility devices, and functional levels. The authors reported that ramp slopes of 1:12 to 1:7 could be negotiated with "relative ease" by 88% of the self-propelling manual wheelchair users (n=18), compared to 52% of the same group for the 1:6 slope.…”
Section: Previous Ramp Researchmentioning
confidence: 99%
“…In a study done with 20 MWUs with various diagnoses, Sanford et al reported that, for a 9 m-long adjustable slope, 85 percent of the participants could climb a slope of 1:12, 80 percent successfully negotiated a 1:10 slope, and only 75 percent managed to ascend a 1:8 slope while propelling their own MWC at a selfselected natural speed [5]. Moreover, other studies confirmed that a substantial number of MWUs are unable to climb steeper slopes: Templer et al reported that only 80 percent of MWUs could manage a slope gradient of 1:10 [6], Sweeney et al mentioned that 88 percent of their participants were able to climb 1:12 to 1:7 slopes [7], and Steinfield et al documented that approximately 50 percent of MWUs tested could propel the full length of a 1:12 ramp measuring approximately 40 m in length [8]. To date, no study has investigated whether these success rates measured during uphill propulsion in a simulated natural environment are comparable with those reached during treadmill propulsion among MWUs.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies that solely study on portable ramps. Sweeney et al [8] concludes that it is not possible to recommend a specific ramp for a specific disability or type of wheelchair and stressing that this recommendation must be based on some factors such as the type of the wheelchair and user's social requirements [8]. A more recent study focuses on wheelchair ramp navigation in frozen conditions by considering elements such as type of ascent and descent strategy, number and severity of obstructions, and average velocity among others [9].…”
Section: Literature Reviewmentioning
confidence: 99%